2022
DOI: 10.15252/embj.2022112012
|View full text |Cite
|
Sign up to set email alerts
|

CBP/p300 and HDAC activities regulate H3K27 acetylation dynamics and zygotic genome activation in mouse preimplantation embryos

Abstract: Epigenome reprogramming after fertilization enables transcriptionally quiescent maternal and paternal chromatin to acquire a permissive state for subsequent zygotic genome activation (ZGA). H3K27 acetylation (H3K27ac) is a well-established chromatin marker of active enhancers and promoters. However, reprogramming dynamics of H3K27ac during maternal-to-zygotic transition (MZT) in mammalian embryos are not well-studied. By profiling the allelic landscape of H3K27ac during mouse MZT, we show that H3K27ac undergoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 74 publications
5
57
0
Order By: Relevance
“…Nonetheless, many genes that did not respond to the depletion of either HAT might be redundantly activated by them. Furthermore, we confirmed previous studies showing that these acetylation marks can be detected to some extent even before the major wave of ZGA in flies ( 13 ), as well as in the transcriptionally inactive mammalian zygote ( 60 ). In particular, we could detect Nejire-dependent marks during the first nuclear divisions (cycles 3 and 4), whereas the Gcn5-dependent H3K9ac mark could be detected at the beginning of the first wave of ZGA (cycle 8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, many genes that did not respond to the depletion of either HAT might be redundantly activated by them. Furthermore, we confirmed previous studies showing that these acetylation marks can be detected to some extent even before the major wave of ZGA in flies ( 13 ), as well as in the transcriptionally inactive mammalian zygote ( 60 ). In particular, we could detect Nejire-dependent marks during the first nuclear divisions (cycles 3 and 4), whereas the Gcn5-dependent H3K9ac mark could be detected at the beginning of the first wave of ZGA (cycle 8).…”
Section: Discussionsupporting
confidence: 91%
“…Their presence could either reflect the transcriptional activity of very early genes or indicate that the binding of Nejire and SAGA/ATAC complexes precedes target gene transcription. Given the high degree of overlap between Nejire-dependent with Zelda-dependent and GAF-dependent genes, we speculate that the early presence of Nejire on chromatin could be important for the later activity of pioneer factors during ZGA, as recently described in other systems ( 60 ).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies revealed the association between HDAC1 and transcriptional repression through its deacetylase activity. 44,45 Our data show the proximity of enhancers occupied by EP300 and HDAC1. Therefore, dynamic H3K27 acetylation at enhancers was closely associated with EP300 and HDAC1, and they were required to write and erase these marks.…”
Section: Discussionmentioning
confidence: 70%
“…Then, the mechanism of VPA on ferroptosis in cisplatin-induced AKI needs further study. HDAC1 and HDAC2, as deacetylases of H3K27Ac are involved in various cellular processes such as apoptosis and DNA replication by regulating acetylation ( Wang et al, 2022 ). As reported in these researches ( Jiang et al, 2020 ; Zhu et al, 2020 ), affecting H3K27Ac attenuate kidney injury after cisplatin.…”
Section: Discussionmentioning
confidence: 99%